2020
DOI: 10.7717/peerj.9120
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hub genes of papillary thyroid carcinoma in the TCGA and GEO database using bioinformatics analysis

Abstract: Background Thyroid carcinoma (THCA) is a common endocrine malignant tumor. Papillary carcinoma with low degree of malignancy and good prognosis is the most common. It can occur at any age, but it is more common in young adults. Although the mortality rate is decreased due to early diagnosis, the survival rate varies depending on the type of tumor. Therefore, the purpose of this study is to identify hub biomarkers and novel therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Second, to verify the results of bioinformatics analysis, the effect of RAB5A knockdown on exosome secretion was assessed experimentally. Due to the pervasive usage of combined scores of the STRING database as a cut‐off value in advance bioinformatics analyses, 54,55 we decided to validate its PPI interactions with different combined scores experimentally as our last objective.…”
Section: Discussionmentioning
confidence: 99%
“…Second, to verify the results of bioinformatics analysis, the effect of RAB5A knockdown on exosome secretion was assessed experimentally. Due to the pervasive usage of combined scores of the STRING database as a cut‐off value in advance bioinformatics analyses, 54,55 we decided to validate its PPI interactions with different combined scores experimentally as our last objective.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing popularity of chip and sequencing technology, comprehensive bioinformatic analysis has become a promising method for exploring disease-related biomarkers and their molecular mechanisms ( Sakharkar et al, 2019 ; Wan et al, 2020 ). For example, Zhang et al found that the adipose tissues of insulin-resistant and non-insulin-resistant patients with obesity had differential expression of a number of genes, including matrix metallopeptidase 9, interleukin (IL ) 6 , C-X-C motif chemokine ligand ( CXCL ) 8 , C-C motif chemokine ligand 4, and CXCL10 , which are enriched for several functions, including cytokine-cytokine receptor interactions, tumor necrosis factor (TNF) signaling, and pathways in cancer ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MSC-AS1 facilitates the progression of LUAD by sponging miR-33b-5p to up-regulate GPAM 60 . Previous studies also showed that BCL2 Apoptosis Regulator (BCL2) 61 and Cadherin 2 (CDH2) 62 play an important role in the pathogenesis of thyroid cancer. Therefore, the present study further combined these mRNAs with tumor-related lncRNAs and miRNAs in thyroid cancer, providing a basis for studying the common mechanisms of multiple genes in thyroid cancer.…”
Section: Discussionmentioning
confidence: 97%